2014
DOI: 10.1177/1077546314520832
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the nonlinear characteristics of an axially moving string

Abstract: This paper presents an experimental study of the nonlinear characteristics of an axially moving string. An experimental system with a simple configuration, which is similar to a practical application, was built. Two laser sensors were used to monitor the vertical and horizontal vibrations of the moving string under different conditions. Using the Hilbert-Huang transform method, the detailed results of a typical measured data series, which include intrinsic mode decomposition, Hilbert spectrum and marginal spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Accordingly, mathematical modeling and vibrational analysis of these applicable structures have attracted much attention in recent decades [3][4][5]. In this field, a limited number of 2 of 23 experimental studies have been performed and compared with the theoretical analyses [6,7]. These investigations revealed that engineers could appropriately trust the results of computer simulations and mathematical modeling techniques [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, mathematical modeling and vibrational analysis of these applicable structures have attracted much attention in recent decades [3][4][5]. In this field, a limited number of 2 of 23 experimental studies have been performed and compared with the theoretical analyses [6,7]. These investigations revealed that engineers could appropriately trust the results of computer simulations and mathematical modeling techniques [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Even though it requires more computation time, EEMD, in which finite-amplitude white noises are added to the series to be processed and ensemble means as decomposition results, was chosen for this analysis to avoid possible inter-wave modulations and to suppress possible intermittence. 32,33,36 3.…”
Section: Time-frequency Analysismentioning
confidence: 99%
“…The detailed calculation procedures can be found in. 32,33,35,36 Time-frequency features such as HSP, MSP, and energized IMFs and IFs were extracted.…”
Section: Main Component Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional effects on these processes can be rendered by axial forces in the string [10,17]. In this case, the most influential axial force can be resolved into a vertical force or weight on bit (WOB) and a near-zero transverse component called the bit imbalance force.…”
Section: Frequency Analysis Of Drill Bit Whirlings On Uneven Bottoms mentioning
confidence: 99%